AN INVESTIGATION INTO ELIMINATION OF CYANIDE FROM UNDER PROCESS SOIBUM - THIYAM MINA DEVI,; S. GIRI SINGH,; Y. PRAMODA DEVI,; G. A. SHANTIBALA DEVI, (The Bioscan, 2010)
Comparative envisaging into way of elimination of cyanide for two methods of Soibum processing in laboratory as exudate draining (LPS-I) and exudate retaining (LPS-II) were studied. The rate of release of HCN ranges from 6.05 - 0.37 μg/hr/100g and 4.13 - 0.17 μg/hr/100g from the fermenting mash upto day 360 of LPS-I and LPS-II respectively. In LPS-I, HCN was also eliminated from the fermenting mash by dissolution as exudate that had been drained out and collected on intermittent days. The volume of exudation went on decreasing with time, but upto day 60, HCN was found to be increasingly extracted with successive later collection, total volume of exudate per 100 g of mash as on 360 days was 14.18 mL and its HCN content was recorded to be 4551.49 mg. The study reveals that LPS-I plays a major role of sooner elimination of HCN from the fermenting mash than LPSII due to accumulation of exudate which holds a substantial amount of HCN since the onset of fermentation and this might impart to comparatively higher rate of HCN release from the fermenting mash.